Breast Implant-Associated Anaplastic Large Cell Lymphoma With Invasive Chest Wall Masses. Issue 4 (October 2021) - Coombs, Demetrius M.; Aliotta, Rachel; Jagadeesh, Deepa; Raymond, Daniel; Isakov, Raymond
Abstract : Background: Breast implant-associated anaplastic large-cell lymphoma (BIA-ALCL) might occur in any patient with a history of textured breast devices, and often presents as a spectrum of disease: from a simple late-onset seroma, to complex advanced locally aggressive disease with chest wall involvement. The combination of medical therapy and surgical implant removal with complete capsulectomy is believed to be curative. Objectives: In patients with advanced cases, however, and although generalized recommendations exist, no consensus exists regarding the ideal medical and surgical management of those presenting with invasive disease. Methods: This preliminary report describes 2 distinct presentations of rare invasive chest wall BIA-ALCL, both treated successfully, by using a combined medical and surgical multidisciplinary team approach. Subsequently, we discuss considerations and the current literature surrounding the treatment of advanced BIA-ALCL with chest wall and adjacent structure involvement. Results: All patients necessitated chest wall resection and composite reconstruction due to tumor involvement of the thorax with residual hypermetabolic activity, despite chemotherapeutic pretreatment with different neoadjuvant medical therapies. All healed well after surgery and experienced resolution of symptoms without signs of relapse on regular follow-up. Conclusions: In the rare subset of patients presenting with invasive BIA-ALCL, the question persists as to which systemic treatment remains optimal. However, the evidence supports multiple, particularly in combination with surgical extirpation and reconstruction. Here we present 2 proven treatments, both in timing and modalities chosen, as part of the first step to establish a formally accepted treatment paradigm for advanced BIA-ALCL patients with invasive chest wall involvement.